A model for an application to biomedical engineering through nanoparticles. (October 2016) - Hayat, T.; Nawaz, Sadaf; Alsaadi, F.; Rafiq, M.; Mustafa, M.
Highlights: Slip effects on the peristaltic motion of water based nanofluid in asymmetric channel. Velocity slip and temperature jump conditions are employed. Five different types of nanoparticles are used: Cu, Ag, CuO, Al2 O3, TiO2 . Comparative study for two different models of effective thermal conductivity is presented. Abstract: Recent advancements in nanoscience and technology has made the nanofluid an important research topic. Various models have been put forward to estimate the effective thermal conductivity of nanofluids. Present article addresses the comparative study of Maxwell's and Hamilton–Crosser's model for mixed convection peristaltic flow of incompressible nanofluid in an asymmetric channel. Viscous dissipation and heat generation/absorption effects are retained. Analysis is performed for five different types of nanoparticles namely titanium oxide or titania (TiO2 ), aluminum oxide or alumina (Al2 O3 ), copper oxide (CuO), copper (Cu) and silver (Ag) with water as base fluid. Velocity and thermal slip conditions are employed. Lubrication approach is adopted for problem formulation. The developed non-linear problems are solved numerically. Plots for axial velocity, temperature and heat transfer rate at the wall are obtained and analyzed.